Interfacial reaction and shear strength of Ni-coated carbon nanotubes reinforced Sn–Ag–Cu solder joints during thermal cycling - Nai, S. M. L. (2013)
In this study, varying weight percentages of Ni-coated carbon nanotubes (Ni-CNTs) were incorporated into Sn–Ag–Cu (SAC) solder matrix, to form composite solders. Up to 0.05 wt.% of Ni-CNTs were successfully incorporated. The interfacial microstructure and shear strength of solders on Ni/Au finished Cu substrates were investigated after thermal cycling (from −40 °C to +125 °C) for up to 2000 cycles. The thermomechanical property results showed an improvement in thermal stability for the composite solders. Results also revealed that after soldering and thermal cycling, the interfacial IMC thickness of the unreinforced solder joint was observed to grow more significantly than that of the composite solder joints. Shear tests results revealed that both composite solder joints which were thermally cycled and as-soldered had better ultimate shear strength than their monolithic counterparts. The shear strength of all thermally cycled solder joints decreased with increasing thermal cycles.